Risk for Femoral Fractures in Parkinson’s Disease Patients with and without Severe Functional Impairment - Benzinger, Petra (Public Library of Science, 2014)
BACKGROUND: Impaired balance is a major problem in patients with idiopathic Parkinson’s disease (PD) resulting in an increased risk of falls and fall-related fractures. Most studies which analyzed the risk of femoral fractures in patients with idiopathic PD were performed either in specialized centers or excluded very frail patients. The current study used a large population-based dataset in order to analyze the risk of femoral fractures in patients with idiopathic PD. METHODS: Data from more than 880.000 individuals aged 65 years or older and insured between 2004 and 2009 at a large German health insurance company were used for the analyses. Persons with idiopathic PD were identified by the dispensing of Parkinson-specific medication and by hospital diagnoses, if available. People without PD served as the reference group. Incident femoral fractures were obtained from hospital diagnoses. Analyses were stratified by gender and information on severe functional impairment (care need) as provided by reimbursement claims. RESULTS: Compared with the reference group, persons with idiopathic PD had a more than doubled risk to sustain a femoral fracture. The risk was higher in men (HR = 2.61; 95%-CI: 2.28–2.98) than in women (HR = 1.79; 95%-CI: 1.66–1.94). The increased risk was only observed in people without severe functional impairment. The sensitivity analysis using a refined definition of idiopathic PD patients yielded similar results. CONCLUSION: The findings confirm the increased risk of femoral fractures in patients with idiopathic PD. The relative risk is particularly high in male PD patients and in patients without severe functional impairment.